UPAYA PENANGGULANGAN TINDAK PIDANA PERDAGANGAN PEREMPUAN (TRAFFICKING WOMEN) DI KOTA BANDAR LAMPUNG - Firganefi, Firganefi (Fakultas Hukum Universitas Lampung, 2010)
The research studies the prevention of criminal act of trafficking in women. The research methodology is normative jurisdiction (yuridis normative) and empirical jurisdiction (yuridis empirs) approach. The result of research indicates that the prevention effort was done by using penal and non panel facilities which were including police duty with repressive aspects, it has role as investigating officer and preventive aspect that police role gives protection, service, guidance, information, raid by police to society and reconciliation and also work together with related departments. The factors which obstruct this prevention effort are the followings as; a) law ordinance factors, b) law enforcement, c) society law culture.